1997
DOI: 10.1557/proc-487-33
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Grain Boundaries, Twin Boundaries and Te Precipitates in Cd1−xZnxTe Grown bY High-Pressure Bridgman Method

Abstract: Grain boundaries and twin boundaries in commercial Cd1−xZnxTe, which is prepared by a high-pressure Bridgeman technique, have been investigated with transmission electron microscopy, scanning electron microscopy, infrared-light microscopy and visible-light microscopy. Boundaries inside these materials were found to be decorated with Te precipitates. The shape and local density of the precipitates were found to depend on the particular boundary. For precipitates that decorate grain boundaries, their microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…1, 2 Over the last decade, the methods for growing high quality CZT have improved the quality of the produced crystals however there are material features that can influence the performance of these materials as radiation detectors. The presence of structural heterogeneities within the crystals, such as twinning, pipes, grain boundaries (polycrystallinity), and secondary phases (SPs) [3][4][5][6][7][8][9][10][11] can have an impact on the detector performance. There is considerable need for reliable and reproducible characterization methods for the measurement of crystal quality.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 Over the last decade, the methods for growing high quality CZT have improved the quality of the produced crystals however there are material features that can influence the performance of these materials as radiation detectors. The presence of structural heterogeneities within the crystals, such as twinning, pipes, grain boundaries (polycrystallinity), and secondary phases (SPs) [3][4][5][6][7][8][9][10][11] can have an impact on the detector performance. There is considerable need for reliable and reproducible characterization methods for the measurement of crystal quality.…”
Section: Introductionmentioning
confidence: 99%
“…Specific sites along the grain boundaries and twin boundaries were seen to act as preferential nucleation sites (i.e. triple junctions of grain boundaries, jogs in the twin boundaries) [117][118][119][120]. Experiments show good correlation between the spatial distribution of Te-particles and existing dislocation networks (chuck's work).…”
Section: Defect Generation During Crystal Growthmentioning
confidence: 99%
“…The Te inclusions have an elongated plate or saucer shape within grain boundaries; but even here, they tend to line up with neighboring grains and form sharp boundaries. 21 There is significant evidence that Te inclusions and the surrounding defect field have a strong detrimental effect on electron transport in CdZnTe crystals and on the poor performance of the fabricated detector devices. 22,23 It was also shown that the region of degraded charge transport near Te inclusions extends well beyond the volume of the inclusions themselves.…”
Section: Structural Propertiesmentioning
confidence: 99%